1995
DOI: 10.1161/01.hyp.26.6.1121
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ambulatory 24-Hour Blood Pressure in Patients With High Normal Blood Pressure and Exaggerated Systolic Pressure Response to Exercise

Abstract: Few studies have investigated the significance of abnormal increases in systolic pressure during exercise in patients with high normal blood pressure and its correlation with 24-hour ambulatory blood pressure monitoring and left ventricular structure. This study was performed in 30 sedentary subjects (42 +/- 4 years old) with high normal blood pressure. Fifteen subjects presenting < 220 mm Hg systolic pressure during ergometric exercise were compared with 15 others with systolic pressure > or = 220 mm Hg. Aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
2
15
0
2
Order By: Relevance
“…The increasing in the left atrium dimension was higher in individuals classified in top tertile, and the increasing in the posterior wall thickness tended to be higher. Taking together, our findings and those of cross-sectional studies that identified a higher frequency of end-organ damage in subjects with a hypertensive response [1][2][3]17,[21][22][23] demonstrate that individuals with hypertensive response in the ETT are in a tracking to the full development of hypertension and its consequences. The higher increasing in left atrial dimension and posterior wall thickness in individuals classified at the top tertile of blood pressure response suggest that this condition confer an additional risk for the development of structural cardiac abnormalities.…”
Section: Discussionsupporting
confidence: 68%
“…The increasing in the left atrium dimension was higher in individuals classified in top tertile, and the increasing in the posterior wall thickness tended to be higher. Taking together, our findings and those of cross-sectional studies that identified a higher frequency of end-organ damage in subjects with a hypertensive response [1][2][3]17,[21][22][23] demonstrate that individuals with hypertensive response in the ETT are in a tracking to the full development of hypertension and its consequences. The higher increasing in left atrial dimension and posterior wall thickness in individuals classified at the top tertile of blood pressure response suggest that this condition confer an additional risk for the development of structural cardiac abnormalities.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, studies have suggested that 24-h ambulatory BP have stronger associations with carotid atherosclerosis than resting BP alone [15,16]. An exaggerated BP response to exercise is significantly associated with increased average 24-h ambulatory BP or daytime SBP [10] and mental stress [24], which is a better predictor of targetorgan diseases than a single office BP record [25]. This suggests that stress-induced hyper-reactive BP changes can add clinically relevant information related to the risk of end-organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…An exaggerated blood pressure (BP) response to exercise is also related to impaired arterial function [6,7], structural changes in cardiovascular organs [8,9], and increased average 24-h ambulatory BP [10]. Furthermore, studies have suggested that an exaggerated SBP response to exercise is associated with target-organ damage, such as left ventricular hypertrophy [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These results reinforce the hypothesis of a sympathetic hyperreactivity in HR individuals 4 , corroborated by the elevation of the diurnal parameters and their normality during sleep. Lima et al 24 observed BP values during the wakefulness period, during sleep and in 24 h, as well as mean BP in 24 h that were significantly higher in HR individuals.…”
Section: Discussionmentioning
confidence: 95%